Sharia Value Logic as the Old Value Logic: Second Order Research - Mursid, Mansur Chadi; Aziz, Hassanuddeen B Abd (UIN K.H. Abdurrahman Wahid Pekalongan, 2020)
Concept of value is the old scince, but now especially in Islamic marketing interested to study again. To analyze shariah value logic as the old value logic by literature study, we proposed shariah value logic as mediating role between innovation and performance. Quantitatified shariah value logic (SVL) have examined, in this paper explored SVL from the theory of value to building the new value of innovation. Second order NPD innovation and NPD performance developed in this study. Research limited in building concepts, future research can exploring determinants and consequences of the shariah value logic.